2019
DOI: 10.31729/jnma.4420
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Pregnant Women regarding Oral Health in A Tertiary Care Hospital in Nepal

Abstract: Introduction: Poor dental hygiene has been associated with various perinatal complications in studiesdone worldwide but few studies in Nepal have explored the knowledge of pregnant ladies regardingdental hygiene. The aim of the study was to know the knowledge and practices of pregnant womenregarding oral health in a tertiary care center in Nepal. Methods: A qualitative study was carried out in Nobel Medical College and Teaching Hospital fromJanuary 15, 2018 to June 15, 2018 after approval from the Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
3
10
2
3
Order By: Relevance
“…40 Unfortunately, only 59.4% of the medical practitioners agree that periodontal problems could affect pregnancy outcomes 40 and only 12% of women acknowledge that poor oral health may contribute to low birth weight babies. 38 The plaque index in our study was found to be 0.55. Pregnant women may nd tooth brushing to be nearly impossible, especially in premolar & molar areas because of the pregnancy-related nausea.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…40 Unfortunately, only 59.4% of the medical practitioners agree that periodontal problems could affect pregnancy outcomes 40 and only 12% of women acknowledge that poor oral health may contribute to low birth weight babies. 38 The plaque index in our study was found to be 0.55. Pregnant women may nd tooth brushing to be nearly impossible, especially in premolar & molar areas because of the pregnancy-related nausea.…”
Section: Discussionsupporting
confidence: 45%
“…Most women brushed once daily as seen in Nepal. 38,39,47,48 Our study showed no association between gingival index and oral hygiene habit or frequency of brushing.…”
Section: Occupationcontrasting
confidence: 51%
See 1 more Smart Citation
“…This finding was in line with Gupta et al . [ 32 ] and Avula et al .’s[ 27 ] studies, thus, an intensified education paves an important insight into the improvement of knowledge and reduces suffering. The majority of the study subjects had low oral health knowledge scores irrespectively of a number of pregnancies which could be attributed to the low mean age of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Peningkatan pengetahuan merupakan pendukung untuk terbentuknya sikap positif terhadap perubahan termasuk perilaku Kunjungan antenatal care namun demikian pada penelitian ini menyatakan hasil yang sebaliknya yaitu pada masing-masing variabel terikat yaitu pengetahuan, sikap dan perilaku tidak ada nilai yang kurang dari 0.05 yang artinya tidak ada perbedaan antara antara penghasilan tinggi maupun rendah terhadap pengetahuan, sikap dan perilaku tentang kunjungan antenatal care di puskesmas belakang padang Batam (23).…”
Section: Pengaruh Variabel Luar (Pendidikan Penghasilan Dan Pengetahuan Sebelumnya) Terhadap Variabel Terikat (Pengetahuan Sikap Dan Periunclassified